Impact of Covid-19 on the survival of Igbo owned businesses in Nigeria: the nexus - Osita Fabian Chinedu; Maduka Olisaemeka Dennis; Nkechi Chikwuemeka-Onuzulike (International Journal of Financial, Accounting, and Management, 2020)
Purpose: This study determined the impact of covid-19 on the survival of Igbo owned businesses in Nigeria. Research methodology: The research adopted a survey research design. The population of the study was 50, while census method was adopted. Source of data was questionnaire, which was tested for reliability using Split-Half technique and the value obtained was .863. The analysis was carried out using Regression Technique and a 5% level of significance was used in the hypothesis test. Result: Findings indicated that there is a relationship between restriction of movement and business sustainability (r = .983) and the coefficient of determination shows that a 96% change in the sustainability of Igbo owned businesses is explained by changes in restriction of movement. Limitations: The narrowing of the scope of the study to only importers of goods in Anambra state limits the generalizability of the study. Contribution: Nigerian government will by this study know how to encourage businesses to survive after a pandemic such as covid-19. Also, small business will gain from this study in that they will know from the suggestions made, how to navigate through tough times in their businesses by embracing online platforms to import or supply products. Keywords: SMEs, Coronavirus, Business sustainability, Igbo owned businesses, Restriction of movement